1997
DOI: 10.1121/1.420891
|View full text |Cite
|
Sign up to set email alerts
|

Near-field polarization processing of ice fracturing events

Abstract: As part of the ONR Sea-Ice Mechanics Initiative (SIMI) experiments in the spring of 1994, arrays of high-resolution seismic sensors were deployed in areas of high seismicity identified by real-time processing of acoustic emission events recorded by a wide, horizontal aperture hydrophone array. One of the areas most rich in ice events was located on a small ice floe (∼100×100 m) 4 km Northeast of the main camp, where the seismic array consisting of five 3-component geophones in a 70-m aperture pentagon was depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[1][2][3][4][5]9 This paper will not consider the general theory; however, a basic description of the fundamental seismic wave types is required. Acoustic energy from an underwater source is transmitted to an ice-mounted geophone both as seismic plate waves propagating along the ice ͑due to acoustic energy transmitted into the ice between source and receiver͒, and as acoustic waves that arrive at the underside of the ice directly below the geophone and couple locally into seismic waves.…”
Section: A Ice Seismic Wavesmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5]9 This paper will not consider the general theory; however, a basic description of the fundamental seismic wave types is required. Acoustic energy from an underwater source is transmitted to an ice-mounted geophone both as seismic plate waves propagating along the ice ͑due to acoustic energy transmitted into the ice between source and receiver͒, and as acoustic waves that arrive at the underside of the ice directly below the geophone and couple locally into seismic waves.…”
Section: A Ice Seismic Wavesmentioning
confidence: 99%
“…While a number of previous studies have been reported that used ice-mounted geophones to investigate sources within the ice layer, e.g., ice cracking and ridging, [1][2][3][4][5] relatively little work has been published considering acoustic sources in the water. The approach to bearing-estimation developed here is based on measuring ice seismic waves for which the direction of wave oscillation ͑particle motion͒ is oriented radially outward from the source.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation